Fractal Characteristics Of Soils At USM Campus - Ng, Han Tiong (Universiti Sains Malaysia, 2006)
Fractals are a concern new geometry to describe the variety of natural soil structures. Better understanding for the material properties can be obtained by the development in fractal geometry. A case study was carried out at the USM, Engineering Campus in Nibong Tebal, Malaysia to determine the mass fractal dimension in that area and some relationship that related to the mass fractal dimension was analyzed. Fifty soil samples were taken at various locations in USM, Engineering Campus. These soil samples were separated into two categories which are disturbed area soil samples and undisturbed area soil samples. The particle size distributions of these samples were analyzed and the mass fractal dimensions of these samples were determined. Two relationships which related to the mass fractal dimension were carried out, there were: (i) relationship between mass fractal dimension and the soil properties and (ii) relationship between mass fractal dimension and land disturbance. Four soil properties that use in the analysis were moisture content, bulk density, organic content and clay content. The results for the relationship between mass fractal dimension and soil properties were good and similar to the theory. From the analysis of the land disturbance, the mass fractal dimension for the undisturbed area was higher than the mass fractal dimension for the disturbed area.